Innate immune complexity in the purple sea urchin: diversity of the Sp185/333 system - Smith, L. C. (Frontiers in Immunology, 2012)
The California purple sea urchin, Strongylocentrotus purpuratus, is a long-lived echinoderm with a complex and sophisticated innate immune system. Several large gene families that function in immunity in this species includes the Sp185/333 gene family with ~50 (±10) members. The family shows intriguing sequence diversity and encodes a broad array of diverse yet similar proteins. The genes have two exons of which the second encodes the mature protein and has repeats and blocks of sequence called elements. Mosaics of element patterns plus SNPs within the elements result in significant sequence diversity among the genes yet maintains similar structure among the members of the family. An Sp185/333-positive BAC insert has a cluster of six, tightly linked Sp185/333 genes that are flanked by GA microsatellites. The sequences between the GA microsatellites are much more similar to each other than are the sequences outside the microsatellites suggesting processes such as gene conversion, recombination, or duplication. However, close linkage does not correspond with greater sequence similarity compared to randomly cloned and sequenced genes that are unlikely to be linked. There are three segmental duplications that are bounded by GAT microsatellites and include three almost identical genes. RNA editing is detectible throughout the messages and putative post-translational modifications to the proteins result in broad arrays of Sp185/333 proteins that differ among individuals. The mature proteins have an N-terminal glycine-rich region, a central RGD motif, and a C-terminal histidine-rich region. The Sp185/333 proteins are localized to the cell surface and are found within vesicles in subsets of polygonal and small phagocytes. The coelomocyte proteome shows full-length and truncated proteins, including some with missense sequence. Current results suggest that both native and a recombinant Sp185/333 protein bind bacteria and are likely important in sea urchin innate immunity.